Review: Russian Orthodoxy on the Eve of Revolution - Binns, John (The journal of theological studies, 2005)
Russian Orthodoxy on the Eve of Revolution Vera Shevzov xiv + 358 Illustrated. New York Oxford University Press 2004 0 19 515465 7 £30